Die Polen angesichts der Umbrüche im politischen und gesellschaftlichen Bereich. Ein Vierteljahrhundert nach der Unabhängigkeit Polens - Józef Stala (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2015)
Financial, political, ideological, sociological, cultural and existential transitions in Poland are experienced as a far more complex process than what it seemed in the begin - ning. The challenges Poles are facing in a new, democratic society, in some ways, are more demanding than those in a socialist one. In this article, the author presents sociological data, gathered by the Public Opinion Research Centre in Poland, showing the public opinion about the change in the system since 1989. The evaluation of the social consequences of transformation is not unequivocal. 37% believe that the post-1989 changes brought more benefits than losses to the people. On the negative side, Poles note the increase in indi - vidualism and weakening of interpersonal ties. Negative public sentiment grew in Poland especially after 2009, five years after Polish accession to the European Union when the average salary of Poles accounted for about 25–30% of earnings in Western Europe, many people could not find employment in Poland and so they had to migrate to Western Europe.